TINGKAT SUHU TAMBANG DALAM DAN KELUHAN SUBJEKTIF PEKERJA TAMBANG DALAM PT. AIC JAYA KOTA SAWAHLUNTO - Sesmeri Haryani (Ensiklopedia of Journal, 2020)
PT. AIC Jaya is a company located in Sawahlunto City in the mining sector using deep mining techniques. Setting the temperature or temperature of the work environment to support work productivity. The purpose of this study was to determine the description of deep mine temperature levels and subjective complaints of underground mining workers at PT. AIC Jaya, Sawahunto City. The design of this research is descriptive in July 2018 with the number of respondents 56 people. Data processing with editing, coding, entry, cleaning. Primary data in this study were obtained from measurements of deep mine temperatures and questionnaire distribution to determine subjective complaints. The results obtained in the highest temperature of 25.9 oC and the lowest 24.9 oC with the most complaints, that is, a lot of sweat and thirst quickly. The company is expected to maintain the application of the exhaust ventilation system because it can keep the mine temperature in normal and provide drinking water to replace lost fluids.